Assessing the Vulnerability of the Betawi Language: A Multidisciplinary Approach toward Preservation amidst Rapid Urbanization - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2023)
The Betawi language, which is the indigenous language of the original inhabitants of Jakarta, is currently in a precarious state due to rapid advancements and changes within the city's social and cultural landscape. This creates an urgent need for robust and effective strategies to conserve this linguistic heritage. The concern is rooted in the fear that the extinction of the Betawi language would result in the failure to transmit valuable Betawi traditions, technology, cultural norms, and customs to subsequent generations. Such a loss would signify the decay of a rich and unique civilization. This study is designed to assess the current health and vitality of the Betawi language, drawing upon the disciplines of Social Semiotics, Demography, and Sociology for its methodological framework. Rather than relying exclusively on quantitative data, this research employs a qualitative approach to capture the subtleties, nuances, and specific preferences related to the language's use and significance. The study's findings point out that the Betawi language is in an even more vulnerable state now than it has been in the past, and this decline has severe ramifications for the Betawi community. Despite these challenges, educational interventions show promise to aid in the preservation of the language. Going forward, it is imperative to develop a well-rounded strategy for the preservation of the Betawi language that involves collaboration from a variety of stakeholders across different sectors